Formalizing drug indications on the road to therapeutic intent. (17th July 2017) - Nelson, Stuart J; Oprea, Tudor I; Ursu, Oleg; Bologa, Cristian G; Zaveri, Amrapali; Holmes, Jayme; Yang, Jeremy J; Mathias, Stephen L; Mani, Subramani; Tuttle, Mark S; Dumontier, Michel
Abstract: Therapeutic intent, the reason behind the choice of a therapy and the context in which a given approach should be used, is an important aspect of medical practice. There are unmet needs with respect to current electronic mapping of drug indications. For example, the active ingredient sildenafil has 2 distinct indications, which differ solely on dosage strength. In progressing toward a practice of precision medicine, there is a need to capture and structure therapeutic intent for computational reuse, thus enabling more sophisticated decision-support tools and a possible mechanism for computer-aided drug repurposing. The indications for drugs, such as those expressed in the Structured Product Labels approved by the US Food and Drug Administration, appears to be a tractable area for developing an application ontology of therapeutic intent.